2008
DOI: 10.1016/j.pain.2007.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Predicting outcome of TENS in chronic pain: A prospective, randomized, placebo controlled trial

Abstract: Fifty-eight percent of the patients in the TENS group and 42.7% of the sham-TENS group were satisfied with treatment result (chi square=3.8, p=0.05). No differences were found for pain intensity. Patients diagnosed with osteoarthritis and related disorders (especially of the vertebral column) or peripheral neuropathic pain were less satisfied with high frequency TENS (OR=0.12 (95% CI 0.04-0.43) and 0.06 (95% CI 0.006-0.67), respectively). Injury of bone and soft tissue (especially postsurgical pain disorder) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
2
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 46 publications
2
29
2
2
Order By: Relevance
“…Placebo-induced expectancies decrease pain and modulate specific neural mechanisms 34, 39, 44. In some studies, placebo TENS has shown similar effects to active TENS 2, 29, 32. Thus, the evaluation of placebo treatment to discerning the true efficacy of active TENS treatment is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Placebo-induced expectancies decrease pain and modulate specific neural mechanisms 34, 39, 44. In some studies, placebo TENS has shown similar effects to active TENS 2, 29, 32. Thus, the evaluation of placebo treatment to discerning the true efficacy of active TENS treatment is essential.…”
Section: Introductionmentioning
confidence: 99%
“…This application protocol was based on previous evidence, which report different and complementary analgesic mechanism when adopting high and low frequencies 9 , 20 , 24 , 26 . The TENS device was connected to a placebo device with a selector key that was switched off, without the volunteers knowing this, in such a way not to allow them to distinguish between test procedure and placebo.…”
Section: Methodsmentioning
confidence: 99%
“…• Laser (low level laser) applied for hypersensitivity over but not in contact with the sensitive region (has been found by the author to reduce hyperaesthesia in some patients). • TENS [11] for home use with a rate of 200 Hz and a width of 80 ms for pain. • Direct current (APS) for inflammation and swelling [12].…”
Section: Treatmentmentioning
confidence: 99%